Determinan Indeks Harga Saham Gabungan (IHSG) Jangka Pendek dan Panjang - Heru Wahyudi; Kanti Rahayu (Penerbit Goodwood, 2022)
Purpose: This study aims to analyze the effect of stock market capitalization and external factors on the Composited Stock Price Index (IHSG). Research methodology: This study uses secondary data with the type of time series data obtained from the publication of the official website of The Otoritas Jasa Keuangan (OJK), U.S. Energy Information Administration (EIA), London Bullion Market Association (LBMA) and Yahoo Finance for the period January 2011 - December 2020. The model used in this study is the Error Correction Model (ECM). Results: The results showed that all independent variables in the short term had a significant effect on The IHSG. Stock market capitalization, world oil prices and The Hang Seng Index have a positive effect, while world gold prices have a negative effect. The Error Correction Term (ECT) has a coefficient of -0.2045 with a significant negative direction with a 5% confidence level. Shows that the Adjustment Mechanism Processes in the long-term balance lasts for 20 months.